ANALISIS PERBANDINGAN PASIR JAMBI DAN PASIR PONTIANAK TERHADAP KUAT TEKAN BETON - Sahat Martua Sihombing; Parlindungan Panjaitan; Achmad Pahrul Rodji (Jurnal Sipil Krisna, 2022)
This study aims to analyze the comparison of Jambi sand and Pontianak sand to the compressive strength ofconcrete. Concrete is a mixture obtained by mixing Portland cement, water and aggregate, which is an additivethat varies greatly from chemical additives. For the construction of roads, bridges, buildings, etc. which are in theconcrete mix. Aggregate is the largest part in the formation of concrete, while cement and water will form a pastethat will bind the aggregate. Concrete is a function of its constituent materials consisting of cement, hydraulic,fine aggregate, water and admixture additives. In this study, there are two types of fine aggregate used, namelyJambi Sand and Pontianak Sand. The quality results of Jambi Sand met the organic standard and test by achievinga result of 3, while the quality of Pontianak Sand on the organic test reached 5, and in terms of specific gravity,Pontianak Sand was better than Jambi Sand. The results of the compressive strength of concrete with Jambi Sandand Pontianak Sand were found to be stronger with Pontianak Sand with an average of 63.60